An assessment of the quality of mortality and cause of death statistics produced by the civil registration and vital statistics system in Maldives - Sofoora Kawsar Usman; Sheena Moosa; Lene Mikkelsen; Hang Li; Hafizur Chowdhury; Tim Adair (Asia-Pacific Sustainable Development Journal, 2021)
The civil registration and vital statistics system is the most comprehensive source of data on mortality used to inform health policy in Maldives. The objective of this study is to assess the quality of the civil registration and vital statistics data and recommend improvements. The electronic tool ANACONDA was used to evaluate completeness of death registration, plausibility of age-specific death rates, quality of cause of death reporting and generate the Vital Statistics Performance Index for Quality for the period 20102017. The quality of physicians practices in completing the medical certificate of cause of death was evaluated using a standardized assessment tool. Death registration completeness was estimated to be 95.4 per cent for males and 97.0 per cent for females for the 20142017 period. Life expectancy estimates using the civil registration and vital statistics system data varied by three to four years, depending on the population data source used. About half of all deaths were assigned a cause of death that was unclear or not an underlying cause. The Vital Statistics Performance Index was 48.8 for the period 20142017, which is rated as being low quality. Poor medical certification practices were common; for example, more than half (56 per cent) of medical certificates of cause of death had an incorrect or clinically improbable chain of events leading to death. In conclusion, improvement in medical certification practices is necessary to attain more reliable mortality indicators to aid policy and planning.